Performance Evaluation of MAC Layers with Routing Protocols in Wireless Sensor Networks - N.Renjith, P.; Ramesh, K.; Anto Bennet, M.; Reddy, Giridhar (International Journal of Engineering and Technology, 2018)
Enormous innovations in Wireless communication shaped an outstanding enhancement in the arena of Wireless Sensor Networks (WSN). Today, WSN has transformed as an inevitable technology, controls virtually all the applications like ecological monitoring, Security and application that save our lives and possessions. Unlike conventional wired Network, WSN has its own unique characteristics which make WSN distinctive and more feasible. WSN is an infrastructure-less network, utilizes a large range of sensor nodes which are deployed in a specific geographical area of interest to sense and gather information. This information are forward to the base station with the help of routing protocol. Due to Ad-hoc nature of Wireless Sensor Networks, Medium Access Control (MAC) Layer plays a vital role in enables multiple nodes to stake a shared channel securely with slightest collusion and interference. MAC protocol benefits to increase network trustworthiness and efficiency by defining and regulating traffic in every specific channels inside the network. In this paper, we present a performance evaluation of different MAC Layer protocols like 802.11, ALOHA, CSMA, MACA and TDMA with various routing protocols like AODV, DSR, FSR and ZRP in Wireless Sensor Network. This paper compares performance parameters like Throughput, End to End Delay, Packet Delivery Ratio and Battery consumption. This analytical studies opens up with research direction and focuses on key challenges in selecting routing protocol and MAC layer to improved Network efficiency and reliability.Â